+0  
 
+1
63
2
avatar+59 

f(x) = 2x+1
g(x)= 3x-2

Find: 

a) f-1(x), the inverse function
b) f(g(x)), a composition
c) g(f(x)), another composition
d) 2f(g(x)) = 3g(f(x))

 Jan 20, 2021
edited by Guest  Jan 20, 2021
 #1
avatar+116126 
+2

a)   Inverse of  f

Get x by itself,  "swap"  x and y

 

y =2x  + 1

y-1   =2x

(y -1)  / 2  = x

(x - 1) / 2  = y     =   the inverse

 

 

b)   f(g)     we are putting   g into  f

 

f(g) = 2( 3x  - 2)  + 1  =   6x - 4  + 1  =   6x  - 3

 

c) g(f).....just the other way around.....we  put  f into  g

 

g(f)  =  3( 2x + 1)  - 2  =   6x + 3 - 2   =  6x  + 1  

 

d)  2f(g)  =3g (f)

 

2 (6x - 3)  = 3(6x + 1)

 

12x  -  6 =  18x  +  3

 

12x - 18x  =  3 + 6

 

-6x  =   9      

 

x =  9/-6  =   -3/2

 

 

cool cool cool

 Jan 20, 2021
 #2
avatar
+1

Thank u very much!

Guest Jan 20, 2021

85 Online Users

avatar
avatar
avatar
avatar
avatar